Day-of-the-week Effect on Stock Markets in the Region - Milošević Avdalović, Snežana (Industrija, 2018)
This research examines calendar anomalies (day-of-the-week effect) on stock exchanges in the region. The main objective of the study is to examine the effect of days of the week on stock exchanges in the region in the period from 2008 to 2014, and whether there are differences in relation to the effects that occur during the crisis period from 2008 to 2011 and post-crisis period from 2012 to 2014. The subsample of the analysis shows different results due to an increase in the maturity of the capital market, the financial crisis, accession to the European Union and other important events for the financial markets in the region. The purpose of this paper is to determine whether the relationships between the average stock returns in emerging markets are the same or different across different days of the week. The study includes a quantitative analysis of the yield of stock exchange indices on a certain day that uses daily data from 01.01.2008 to 31.12.2014 for capital markets in Bosnia and Herzegovina, Bulgaria, Montenegro, Croatia, Macedonia, Romania and Serbia. The results of the study indicate the effect of the days of the week on all observed stock markets in the region, except for the stock market in Bulgaria. Obtained panel results support earlier studies conducted on emerging markets and provide evidence of stock market inefficiency.